Perfiles económicos y comportamiento del gasto en salud de los hogares con personas adultas mayores - Ceballos Mina, Owen Eli (El Colegio de México A.C., 2019)
This article estimates non-parametric models for the economic and health expenditure behavior of families with older adults in Mexico. Using information from the 2016 Household Income and Expenditure Survey, household consumption patterns are described in conjunction with the age of the head of household as a representation of the family life course. The results show that the presence of the older adult population in households is linked to an approximately 50% increase in health spending and the corresponding financing through the increase in monetary savings flows throughout the life cycle. Evidence is also provided of the importance of social security in reducing the volatility of health spending during the advanced stages of the life course.